Budget and constitution: a proposal for revision in the light of the Maastricht Treaty - MASERA, R.S. (PSL Quarterly Review, 2013)
The problems regarding Italy's proposed adherence to the European Economic and Monetary Union are discussed, particularly, the procedures in determining the public budget and their possible changes. Transparency in the budget process is needed to be able to do this task. The implications of the proposed changes on the amendments to the Finance Bill and the consequences of the Maastricht Treaty should also be closely examined. The economic and legal rules must be made known well before switching to the European currency. JEL Codes: F15, H61